2022
DOI: 10.1016/j.susoc.2021.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A modified UTAUT model for the acceptance and use of digital technology for tackling COVID-19

Abstract: COVID-19 pandemic expedites the development of digital technologies to tackle the spread of the virus. Several digital interventions have been deployed to reduce the catastrophic impact of the pandemic and observe preventive measures. However, the adoption and utilisation of these technologies by the affected populace has been a daunting task. Therefore, this study carried out exploratory investigation of the factors influencing the behavioural intention (BI) of people to accept COVID-19 digital tackling techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 89 publications
6
45
1
6
Order By: Relevance
“…Thirdly, community influence in UTAUT is the users' perception surrounding groups' attitudes toward a technology (Jadil et al, 2021 ). Relevant studies have uncovered that community influence directly or indirectly impacts online learners' Willingness To Use (WTU) (Akinnuwesi et al, 2021 ). This study contends that external factors, such as school fellows, teachers, and parents, significantly impact online learners' WTU.…”
Section: Online Chinese Learning (Ocl)-oriented Learning Satisfaction...mentioning
confidence: 99%
“…Thirdly, community influence in UTAUT is the users' perception surrounding groups' attitudes toward a technology (Jadil et al, 2021 ). Relevant studies have uncovered that community influence directly or indirectly impacts online learners' Willingness To Use (WTU) (Akinnuwesi et al, 2021 ). This study contends that external factors, such as school fellows, teachers, and parents, significantly impact online learners' WTU.…”
Section: Online Chinese Learning (Ocl)-oriented Learning Satisfaction...mentioning
confidence: 99%
“… 24 Boluwaji et al adopted the UTAUT model to study the factors influencing users to accept COVID-19 digital tackling technologies. 25 …”
Section: Literature Reviewmentioning
confidence: 99%
“…24 Boluwaji et al adopted the UTAUT model to study the factors influencing users to accept COVID-19 digital tackling technologies. 25 Prior studies have analyzed the user's willingness of accepting digital health information system or online medical by using TAM and UTAUT and revealed that several factors, such as self-efficacy, effort expectancy and performance expectancy, influence users' behavior and intention. These findings can be regarded as contributions to understanding the user's willingness of accepting digital health information system or online medical.…”
mentioning
confidence: 99%
“…Hence, we posit that: H8: Alignment of EMR technology with business defined critical success factors will positively influence user decision to adopt EMR Previous studies have highlighted key innovation diffusion factors which include relative advantage and emphasised the impact of relative advantage on user perception of usefulness of new technology (30). Therefore, we posit that: H9: Relative advantage positively mediates user decision to adopt and use EMR Research has shown that age, gender and years of experience of users can have an impact on their decision to adopt and use new technology (31). Moreover, users that are already comfortable with a particular system or way of working for years might be reluctant to change and adopt a new system (30).…”
Section: Introductionmentioning
confidence: 96%
“…Research has shown that age, gender and years of experience of users can have an impact on their decision to adopt and use new technology ( 31 ). Moreover, users that are already comfortable with a particular system or way of working for years might be reluctant to change and adopt a new system ( 30 ).…”
Section: Introductionmentioning
confidence: 99%